A traction load modeling method of metro trains based on the regenerative braking energy effective utilization and its application - SHI Dan; GAO Dongsheng; YANG Rui (机车电传动)
Currently, many metro lines use ground energy storage facilities to gather regenerative braking energy of trains. The capacity configuration of the energy storage facility is closely associated with the characteristics of regenerative braking power of traction load in the power supply section. However, traditional diode rectifier unit of traction substation cannot transmit the regenerative braking energy back to the power grid, thus bringing difficulties in obtaining the data of regenerative braking power of the traction power supply section through field testing, so the configuration of the capacity of energy storage device lacks data support. This paper proposed a traction load modeling method based on the probability distribution of single train power and the probability distribution of the number of trains in the power supply section, and traction load simulation was used to realize the multiple-target optimization configuration of energy storage facility capacity. This method first established the power probability distribution model of a single train under different working conditions, and then used Poisson distribution to model the number of trains in the power supply section, and then obtained the traction load model considering the time sequence of train. At last, artificial fish swarm algorithm was used to identify the parameters of the proposed traction load model. The probability density of the positive part of traction load power generated by detailed example was compared with the measured data, and the results had verified the accuracy and validity of the modeling.